2022
DOI: 10.47329/jurnal_mbe.v8i1.844
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kepercayaan, Kualitas Produk, dan Kepuasan Konsumen terhadap Repurchase Intention Di Tokopedia

Abstract: Repurchase intention oleh konsumen merupakan salah satu sasaran dari sebuah perusahaan untuk aktivitas bisnis yang berkelanjutan. Faktor intenal dan eksternal perusahaan akan mempengaruhi konsumen dalam menentukan keputusan tersebut. Penelitian ini bertujuan untuk mengetahui pengaruh parsial dan simultan dari kepercayaan, kualitas produk dan kepuasan konsumen terhadap repurchase intention di Tokopedia. Sampel penelitian ini ditentukan menggunakan teknik pengumpulan non probability sampling dan metode purposive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…Penelitian yang dilakukan Zaid menunjukkan kepuasan pelanggan meningkatkan pembelian ulang suatu produk (Zaid, 2020). Sejalan dengan hal tersebut, penelitian yang dilakukan Wijayanthi menunjukkan adanya pengaruh kepuasan pelanggan terhadap repurchase intention (Putri Ayu Wijayanthi & Widya Goca, 2022). Semakin tinggi tingkat kepuasan pelanggan peluang untuk adanya pembelian ulang produk akan semakin besar.…”
Section: Pendahuluanunclassified
“…Penelitian yang dilakukan Zaid menunjukkan kepuasan pelanggan meningkatkan pembelian ulang suatu produk (Zaid, 2020). Sejalan dengan hal tersebut, penelitian yang dilakukan Wijayanthi menunjukkan adanya pengaruh kepuasan pelanggan terhadap repurchase intention (Putri Ayu Wijayanthi & Widya Goca, 2022). Semakin tinggi tingkat kepuasan pelanggan peluang untuk adanya pembelian ulang produk akan semakin besar.…”
Section: Pendahuluanunclassified
“…Customers in Denpasar who are satisfied with the products sold by Fore Coffee are more likely to purchase those things again in the future. According to a number of studies (Liang et al, 2018;Bello et al, 2021;Anggraini et al, 2020;Muchlis, 2021;Wijayanti and Goca, 2022), the level of satisfaction a customer has with a product or service has a significant and positive impact on whether or not they intend to buy it again.…”
Section: The Relationship Between Customer Satisfaction and Repurchas...mentioning
confidence: 99%
“…People's purchasing habits have shifted from conventional to technology-based due to the development of internet technology ( (Miandari et al, 2021). Internet technology is now being used extensively not only to meet communication requirements, but also to develop other sectors, such as shopping to meet daily needs, employment, education, and entertainment (Wijayanti and Goca, 2022). As of January 2022, bps.go.id's 2021 Susenas Survey data collection indicated that there were 204,7 million internet users in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Customers in Denpasar who are satisfied with the products sold by Fore Coffee are more likely to purchase those things again in the future. According to a number of studies (Liang et al, 2018;Bello et al, 2021;Anggraini et al, 2020;Muchlis, 2021;Wijayanti and Goca, 2022), the level of satisfaction a customer has with a product or service has a significant and positive impact on whether or not they intend to buy it again.…”
Section: The Relationship Between Customer Satisfaction and Repurchas...mentioning
confidence: 99%
“…People's purchasing habits have shifted from conventional to technology-based due to the development of internet technology ( (Miandari et al, 2021). Internet technology is now being used extensively not only to meet communication requirements, but also to develop other sectors, such as shopping to meet daily needs, employment, education, and entertainment (Wijayanti and Goca, 2022). As of January 2022, bps.go.id's 2021 Susenas Survey data collection indicated that there were 204,7 million internet users in Indonesia.…”
Section: Introductionmentioning
confidence: 99%